Malus Law in terms of the geometric phase - Zdunek, Marzena; Woźniak, Władysław Artur (Photonics Letters of Poland, 2013)
The aim of the present work is the description of the commonly known Malus law as the interference of two waves. We have proposed two cases: interference of two waves with different intensities and equal phases and interference of two waves with different phases and equal intensities. The first case can be realized by decomposition of the polarization state of the light incident on the analyzer into base of linearly polarized waves. In the second case the base of circularly polarized waves should be chosen. This last option allows applying of the geometric phase concept to the Malus law. Full Text: PDF References P. Kurzynowski, W.A. Woźniak, M. Szarycz, "Geometric phase: two triangles on the Poincaré sphere", J. Opt. Soc. Am. A 28, pp. 475-482 (2011). CrossRef W.A. Woźniak, P. Kurzynowski, M. Zdunek, "Malus Law – interferometric interpretation", Opt. Appl. Vol. XLIII, No. 2, (2013). DirectLink